The Intertexuality of Visual Cultural Between Contemporary British Ceramic and Iraqi Ceramic (Godon Baldwen and Saad Shakier ) As An Example: Comparative Study - Majed Abdulnaby Saleh, Abir (Al-Adab Journal, 2020)
Intetexuality in plastic art is considered in general such as ceramic at as they navigate to expose the general and cultural references from one side and self-references that are related to the production of plastic art work specially the art of ceramic and how it deals with human storage from the other .But the studies that do not exit from the experimental circle and personal opinion of the ceramist in dealing with this subject in interrelating and citation and according to the art of Iraqi contemporary ceramic and British contemporary ceramic through visual culture by intertexuality metaphor or the communicative art which influence each other by both countries in their production o plastic arts , specially contemporary ceramic art.